2014
DOI: 10.1021/jp5107108
|View full text |Cite
|
Sign up to set email alerts
|

Structures, Thermal Stability, and Chemical Activity of Crown-Jewel-Structured Pd–Pt Nanoalloys

Abstract: In this work, the equilibrium structures, thermal stability, and chemical activity of crown-jewel (CJ)-structured Pd–Pt nanoalloys with highly symmetric cuboctaheral (Cubo), decahedral (Dec), and icosahedral (Ico) structures are studied by using molecular simulation based on the Gupta empirical potential and density functional theory (DFT) calculations. It is found that both the melting temperature and stability of CJ-structured Pd–Pt nanoalloys with the same size follow the order of Ico > Dec > Cubo, which ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…According to this figure, the first-order phase transition can be identified. It can be observed that the temperature corresponding to the maximum peak value in the heat capacity is in good agreement with a simple jump of the caloric curve. , It can be observed from Figure that for all of the simulated nanoclusters configurational energies and heat capacities are decreased from 200 to 350 K, which indicates structural transformations and instability of yolk–shell structures at higher temperatures. Also, this instability of the yolk–shell regime can be observed from Figure S1 of the Supporting Information, which indicates the volume of void space as a function of temperature, and its results are in good agreement with the mentioned discussion.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…According to this figure, the first-order phase transition can be identified. It can be observed that the temperature corresponding to the maximum peak value in the heat capacity is in good agreement with a simple jump of the caloric curve. , It can be observed from Figure that for all of the simulated nanoclusters configurational energies and heat capacities are decreased from 200 to 350 K, which indicates structural transformations and instability of yolk–shell structures at higher temperatures. Also, this instability of the yolk–shell regime can be observed from Figure S1 of the Supporting Information, which indicates the volume of void space as a function of temperature, and its results are in good agreement with the mentioned discussion.…”
supporting
confidence: 66%
“…It can be observed that the temperature corresponding to the maximum peak value in the heat capacity is in good agreement with a simple jump of the caloric curve. 92,93 It can be observed from Figure 2 that for all of the simulated Figure 1. Snapshots of the atomic arrangement of Au@void@Ag YSNs with variable shells and variable cores including (a) Au13@ void@Ag92, (b) Au13@void@Ag162, (c) Au13@void@Ag252, (d) Au55@void@Ag252, and (e) Au147@void@Ag252 and (f) a schematic illustration of the mentioned YSNs.…”
mentioning
confidence: 81%
“…Bimetallic nanoparticles have received great attention due to their multifunctionalities, selectivity, and activity over monometallic particles, and they are increasingly being applied to various areas, including electronics, optics, catalysis, and magnetics [ 1 , 2 , 3 , 4 , 5 , 6 ]. Bimetallic nanoparticles with different structures, like crown-jewel, hollow, heterostructure, core-shell, alloys, and porous structures, have been synthesized using various techniques, such as chemical methods, hydrothermal, impregnation, sol-gel, spray pyrolysis, and precipitation methods [ 7 , 8 , 9 , 10 , 11 ]. This structural diversity is due to the atomic distribution of the individual metals in bimetals.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Figure 3s ,w hich agrees with the phenomenon observed in our previousw ork. [29] In short, the calculation of D andt he melting points showed that coreshell Ag 42 Co 13 exhibits the highest structural and thermals tability amongt hese Ag-Co nanoalloys with different compositions.…”
Section: Structure and Thermal Stability Analysis Of Ag-co Nanoalloysmentioning
confidence: 94%
“…Therefore, the differentc harge redistributioni nt he Ag 55 , Ag 42 Co 13 ,a nd Ag 12 Co 43 clusters upon Oa dsorption can be used to explain their different adsorption strengths for O. [29]…”
Section: Orr Mechanism Analysis For Ag-co Nanoalloysmentioning
confidence: 99%